PENGATURAN PENYIDIKAN TINDAK PIDANA NARKOTIKA DALAM KITAB UNDANG-UNDANG HUKUM ACARA PIDANA DAN UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA - Irawan, Silvia Andira; Diana, Ledy; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Among the law enforcement officers who also have an important role in the existence of cases of narcotics are Investigators, where investigators are expected to assist the settlement of cases of violations of narcotics crime. The purpose of this thesis writing are: First, the arrangement of the investigation of criminal narcotics in the book of criminal procedural law and narcotics laws, Second, the interest of the national narcotics agency in conducting investigations in the narcotics crime seen from the Criminal Procedure Code and Narcotics laws, Third, the ideal arrangement of the investigation of narcotic criminal acts in the criminal procedure code and narcotic laws.This research is done by using normative approach that is law principles. The type of data used in this study is to use secondary data that is the primary legal material (the 1945 Constitution, the Book of Criminal Procedure), secondary law materials (books related to the research result of the arrangement of the investigation of narcotic criminal acts Based on criminal procedural law and narcotic law), and tertiary law materials (Dictionary of Bahasa Indonesia), data collection techniques using the deductive method is a way of drawing conclusions from general to specific theorems.From the results of research there are three main issues that can be concluded. First, the arrangement of the investigation is done in accordance with the rules (Criminal Procedure Code and Narcotics Act); Secondly, the interest of the national narcotics body in conducting the investigation is: indeed indispensable in conducting narcotics investigation, coupled with the input to make troops Strike force for the prevention and control of narcotics crime, Third, the ideal arrangement of narcotics criminal investigation is: that there is no need for any police investigator who sits as an investigator in the National Narcotics Board because the police investigator has been a sole investigator for all crimes whose authority Not provided by the Narcotics Act. The writer's suggestion, Firstly, there needs to be a bigger budget increase for the process of investigation of narcotics crime, Secondly, for the investigators themselves, to get information about this crime is often done communication and socialization with the community, Third, And provide security guarantees to the public that inform the officer.Keywords: Arrangement-Narcotics-Investigation